An Analysis of The Factors Influencing Customer Satisfaction at Alfamart Minimarkets In The City of Jambi - Amanda Aurelya Putri Rudyan; Hafiati Pracita Sari; Shivani Nayla Putri; Dini Suci Dwi Angraini; Tiara Nur Aulia Azhari; Nayla Felisa Maharani; Yossinomita Yossinomita (Jurnal Administrasi Terapan, 2026)
Customer satisfaction at one of the largest retail chains in Indonesia, Alfamart, is the subject of this study. The main issue in this research is how customer satisfaction is influenced by service, price, accessibility, product completeness, and store cleanliness. The research method is a survey distributed to 107 Alfamart customers who have shopped at the store. The results show that price and service have a significant impact on customer satisfaction, while factors such as accessibility, product completeness, and cleanliness also play a role, although to a lesser extent. The implication of these findings is the importance for Alfamart to continuously improve the quality of service and pricing, as well as ensure cleanliness and product completeness in the store to maintain customer loyalty. This study contributes to the development of business strategies in the retail industry, particularly for companies operating in the supermarket sector.